Shifting away from Russian energy – Alternatives for a more sustainable energy landscape in Finland - Tuisk, Ervin (My University, 2023)
Finland's energy sector has been significantly reliant on Russian fossil fuels, making it subject to supply disruptions and price changes. Finland intended to diversify its energy sources and become more self-sufficient in order to solve these challenges. Simultaneously, EU’s climate plan guided and guides the transition towards a more renewable energy landscape. The goal of this master´s thesis is to assess the evolution of Finland's energy sector following its detachment from Russian energy. The research question is "How will the Finnish energy sector develop after detaching from Russian energy?" To answer this topic, a questionnaire survey of energy experts was undertaken, and three potential scenarios have been created to represent Finland's energy environment in 10 years. The scenarios varied from Finland becoming a net energy importer to being self-sufficient or returning to reliance on Russian energy. The findings indicate that Finland is likely to become more self-sufficient in energy, but there will probably still be energy dependence on other countries. The Finnish energy sector is in a fast shift toward more renewable energy sources, driven by both EU energy security and climate policies, as well as domestic politics. Domestic renewable energy production, particularly wind power, is expected to be the fastest growing sector. Domestic production near to or at self-sufficiency levels is the greatest way to ensure Finland's energy security, reducing reliance on foreign sources that can be manipulated by energy weapon. If necessary, fossil fuels will be imported from countries other than Russia, most likely Norway or the United States. Overall, the Finnish energy sector is undergoing upheaval, and the future appears promising. The Finnish energy sector is anticipated to grow more environmentally friendly and domestic, making it a particularly energy-secure option. Given Finland's strong expertise in creating hydrogen capabilities, the country might be in a global leadership position to hasten the green transition.

Suomen energiasektori on ollut riippuvainen venäläisistä fossiilisista polttoaineista, ja siten altis toimituskatkoksille ja hintamuutoksille. Suomi on pyrkinyt monipuolistamaan energialähteitään ja tulemaan omavaraisemmaksi ratkaistakseen nämä haasteet. Samanaikaisesti EU:n ilmastosuunnitelma ohjaa siirtymää kohti uusiutuvampaa energiamaisemaa. Tämän pro gradun tavoitteena on arvioida Suomen energiasektorin kehitystä sen irrottauduttua venäläisestä energiasta. Tutkielman tutkimuskysymys on: "Miten Suomen energiasektori kehittyy irtauduttuaan venäläisestä energiasta?". Vastauksen saamiseksi tehtiin kyselytutkimus energia-alan asiantuntijoille ja luotiin kolme potentiaalista skenaariota, jotka kuvaavat Suomen energiaympäristöä 10 vuoden kuluttua. Skenaariot energia-aseman suhteen vaihtelevat nettotuojamaan, omavaraisuuden sekä Venäjä riippuvaisuuden välillä. Skenaarioiden ja tutkimusten tulokset osoittavat, että Suomi on todennäköisesti matkalla kohti omavaraisempaa energiakenttää, mutta energiariippuvuutta muihin maihin todennäköisesti tulee silti olemaan. Suomen energiasektori on nopeasti siirtymässä kohti uusiutuvampia energialähteitä. Siirtymää ohjaavat EU:n energia- ja ilmastopolitiikka sekä kotimaiset poliittiset tavoitteet. Kotimaisen uusiutuvan energian tuotannon, erityisesti tuulivoiman, odotetaan kasvavan lähitulevaisuudessa. Kotimaisen tuotannon lisääntyminen on paras tapa varmistaa Suomen energiaturvallisuus, sillä tällöin riippuvuus mistään ulkomaalaisista energialähteistä vähenee. Tarvittaessa fossiiliset polttoaineet tuodaan muualta kuin Venäjältä, todennäköisimmin Norjasta tai Yhdysvalloista. Kaiken kaikkiaan Suomen energiasektori on käymässä läpi suurta murrosta ja tulevaisuus näyttää lupaavalta. Suomen energiasektorin odotetaan kasvavan ympäristöystävällisemmäksi ja kotimaisemmaksi, mikä tekee siitä erityisen energiaturvallisen vaihtoehdon. Ottaen huomioon Suomen vahvan asiantuntemuksen vetyteknologian luomisessa, maa voisi olla globaalissa johtoasemassa vihreän siirtymän nopeuttamisessa.
Keywords: Finnish energy transition, renewable energy, energy politics, geopolitics, energy security, scenarios